REHABILITACJAEffects of excessive body mass on postoperative course and rehabilitation of patients after coronary artery baypass graft - Godula, Ewa; Plewa, Michał; Szurlej, Dariusz; Deja, Marek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Background : Obesity constitutes one of the major risk factor of ischemic heart disease, but based on the available research results it is not clear whether it may also increase the risk of postoperative morbidity and mortality in patients undergoing coronary artery bypass grafting surgery. Extreme obesity itself may also be a contraindication to this invasive procedure. Aim : The aim of the present study was to assess physical and ventilatory capacity in patients undergoing surgical revascularization of heart muscle, in regards to their body mass. Material and methods: The study group included 86 patients, with mean age of 61years (40-80), who were subjected to on-pump coronary artery bypass grafting procedure. Patients’ physical and ventilatory capacity was assessed with 6-minute walk test and spirometry (FEV1, FVC, FEV1/FVC%). The measuremenst were taken the day before and 6 days after the surgery. Subjects were divided into three groups according to their body mass index (BMI): normal weight (A; BMI: 18-24.9 kg/m 2 ; n = 19), overweight (B; BMI: 25-29.9 kg/m 2 ; n = 42) and obese (C; BMI > 30 kg/m 2 ; n = 25). Results: There was a statistically significant drop in values of covered distance and MET value, as well as drop in FEV1 and FVC, and increase of FEV1/FVC% after the surgery. The values of the observed changes did not depend on patients’ BMI, since there were no differences in the length of covered distance, nor in the spirometry variables noted between groups of normal weight, overweight and obese patients. Conclusions : The observed deterioration of physical and ventilatory capacity after CABG procedure seems not to be related to patients’ BMI.